MOTIVASI TIM BOLA VOLLY PUTRI SMA NEGERI 14 PEKANBARU MENGHADAPI O2SN 2017 - M. Fadhli Syafron; Ramadi Ramadi; Aref Va’i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study was conducted to find out the description of the motivation of the state senior high school women’s volley ball team to face O2SN 2017. This type of research is descriptive research using the survey method and collecting information or data using a questionnaire. The population in this study was all volley ball team senior high school 14 pekanbaru a total of 12 athletes. This sampling technique is based on the total sampling technique. The sample used in this study was the women’s volley ball team senior high school 14 pekanbaru with a total of 12 athletes. Based on the results of the study, was obtained the percentage value of the indicators of trainers= 89.08%, headmaster= 83,33%, facilities = 84.08%, parents = 91.92% and the environment = 81.25%, it can be concluded of the motivation women’s volley ball team senior high school 14 pekanbaru to face O2SN 2017 in good category.Key Word : Motivation